"If you just sit at home and look out of the window, then there is no life." an ethnographic study of how home-dwelling people with dementia use the cityscape's life in practice - Mirjam Due Tiemensma; Pernille Tanggaard Andersen; Louise Meijering; Jodi Sturge (Elsevier, 2024)
In the near future, more people with dementia will be living at home within an urban context due to a combination of an increased number of people living with dementia and this past decade's urbanization. A common perception is that home-dwelling people with dementia experience a shrinking world, but emerging research from the UK, Sweden, and the Netherlands has broadened this notion by foregrounding how people with dementia experience neighborhoods as a resource in self-care practices. With this article, we contribute to this emerging body of literature and aim to explore how people with dementia experience the cityscape in relation to the onset and progression of their dementia. This study outlines findings from a 7-month ethnographic study involving 12 home-dwelling people with dementia. Using semi-structured interviews, walking interviews, and photovoice, the study explores how the cityscape of Copenhagen, Denmark, affects the everyday life of home-dwelling people living with dementia. Through thematic analysis, three key themes are identified: interaction with the city's life and space as self-care practices, getting out and about as a way to practice a sense of "being in the world" and the loss of orientation abilities and the changing boundaries of the cityscape. The findings from this study contribute to current discussions concerning how people with dementia experience and perceive city and neighborhood environments.